Guidebook to intellectual property - Jacob, Robin; Fisher, Matthew (London [England] : Hart Publishing, 2022)
"This book is a classic... its style and content remain invaluable." Simon Stokes, Entertainment Law Review This is the new edition of a unique book about intellectual property. It is for those new to the subject, both law students and others such as business people needing some idea of the subject. It provides an outline of the basic legal principles, educating the reader as to the shape of the law. Critically, it also gives an insight into how the system actually works. You cannot understand chess by merely learning the rules - you also have to know how the game is played: so too with intellectual property. The authors deliberately avoid technicalities: keeping things simple, yet direct. There are no footnotes to distract. Although cases are, inevitably, referred to, they are explained in a pithy, accessible manner. The authors try wherever possible to be both serious and light-hearted at the same time. All major areas of IP - patents, trade marks, copyright and designs - are covered, along with briefer treatment of other rights and subjects such as breach of confidence, plant varieties and databases. A novice reader should come away both with a clear outline of IP law and a feeling for how it works. Students will be able to put their more detailed study into perspective. Users will be able to understand better how IP affects them and their businesses."--
Part I Introduction -- 1. Imitation, Monopoly and Control -- 2. Courts, Remedies and Legal Actions -- 3. Patent, Copyright or Design? Part II Protecting the Product -- 4. Patents and How to Get Them -- 5. Important Inventions -- 6. More About Patents -- 7. Industrial Designs Part III Trade Marks, Passing-Off and Unfair Competition -- 8. Trade Marks and Passing-Off -- 9. Trade Mark Registration -- 10. Trade Mark Infringement -- 11. Exceptions to Trade Mark Infringement -- 12. Removal from the Register- Revocation and Invalidity -- 13. Community Marks, International Registration of Marks and Well-Known Marks -- 14. Collective and Certification Marks -- 15. Passing-Off -- 16. Malicious Falsehood Part IV Copyright and Related Rights -- 17. Introduction to Copyright -- 18. Works the Subject of Copyright -- 19. Ownership of Copyright -- 20. What is Infringement of Copyright? -- 21. What is not Infringement? -- 22. Dealings in Copyright -- 23. Moral and Other Related Rights Part V Miscellaneous Matters -- 24. The Criminal Law -- 25. Confidence and Privacy -- 26. Database Right -- 27. The European Community - Free Movement and Competition -- 28. Some Aspects of the International Law of Intellectual Property
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Intellectual property -- Great Britain; Intellectual property; Electronic books